VISUAL THINKING THROUGH MOVIES AND DOCUMENTARIES: ASSESSING STUDENTS’ LEARNING AND SATISFACTION IN AN INTERNATIONAL RELATIONS CLASS (Journal of International Studies, 2025)
In contemporary teaching, it has become quite common to talk about “active learning.” This discussion initially started in Education, but it soon spread to many disciplines. International Relations (IR) is no exception to this trend, with many scholars and teachers reporting on the use of several active learning techniques in their classrooms. An active learning format that has recently gained popularity is “visual thinking” (VT). VT is considered relevant for teaching in many disciplines, including IR. Several scholars have introduced the use of visual items, such as pictures, cartoons, video games, or art paintings, in their teaching projects. Movies and documentaries are also used for visual teaching. Many IR scholars consider them as effective tools to improve students’ learning, thanks to their supposed capacity to make class contents more understandable and increase student class engagement. By relying on a mixed-method approach, the goal of this study is to empirically assess whether a VT format contributes to improving IR students’ hard skills, measured in terms of grades, and their perceptions about and satisfaction with the class.